Selective hydrogenation catalyst as well as preparation method and application thereof
By adopting a three-layer catalyst with a core-transition metal-carbon shell structure, the problems of poor selectivity and insufficient activity in the existing catalysts in the hydrogenation reaction are solved, and high-activity and high-selectivity hydrogenation catalysis is achieved, which is suitable for industrial applications.
Patent Information
- Application Number
- CN202411595896.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2044-11-11
AI Technical Summary
The existing catalysts have poor selectivity, explosive intermediate volume accumulation and precious metal poisoning inactivation in the hydrogenation reaction, and the lack of activity of carbon-cladding materials limits their industrial applications.
A selective hydrogenation catalyst with a three-layer structure of core-transition metal-carbon shell is used to form a carbon shell layer through a combination of a reducing oxide support, transition metal and polymerizable carbon source, and the calcination temperature is regulated to achieve selective catalysis of specific functional groups.
It has achieved high activity and high selectivity hydrogenation catalysis, can withstand CO in environmental O2 and crude hydrogen hydrogen sources, and has excellent industrial application prospects.
Smart Images

Figure CN119565598A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalysts, and in particular to a selective hydrogenation catalyst and a preparation method and application thereof. Background Art
[0002] The corresponding fine chemicals such as aniline / nitrobenzene derivatives, cinnamyl alcohol, citronellol, etc. obtained by hydrogenation reaction of raw materials such as nitroaromatics, cinnamaldehyde, citronellol, etc. are important intermediates in the production of medicines, agricultural chemicals, dyes, pigments, and fragrances. They are important components of fine chemical products and have great application value both in production and in life.
[0003] The Béchamp process has been widely used in the catalytic hydrogenation of nitroaromatics. It requires a large amount of Fe powder, Zn powder, Sn powder, etc. as reducing agents, and a large amount of hydrochloric acid as a solvent, which will cause serious environmental pollution problems and produce a large amount of waste acid and waste residue. Therefore, people have been committed to developing environmentally friendly catalyst systems. Pt-based precious metal heterogeneous catalysts are favored due to their high catalytic hydrogenation activity, as well as their recyclability and environmental friendliness. However, the high hydrogenation activity of Pt-based precious metals also brings about the problem of poor selectivity and the accumulation of explosive intermediate hydroxylamine. It is necessary to use additives such as vanadium and lead phosphate, which brings about separation difficulties. At the same time, if low-cost industrial hydrogen is used as the hydrogen source, it contains a large amount of CO, which causes poisoning and inactivation of Pt-based precious metals, and also limits the application of this type of catalyst in industrial production.
[0004] At present, carbon materials have attracted much attention due to their low cost and simple preparation. Carbon-coated metal or metal oxide materials have also been reported in relevant literature, and the preparation methods include arc method, polymerization method, hydrothermal method, etc. However, the existing materials of this type still have the problem of poor activity, which greatly limits the application of this type of material in industrial production.
[0005] In summary, the preparation of carbon-coated metal or metal oxide materials and their catalytic hydrogenation reaction performance have received extensive attention and research, and have broad application prospects. Summary of the invention
[0006] The purpose of the present invention is to provide a selective hydrogenation catalyst in view of the technical defects existing in the prior art.
[0007] Another object of the present invention is to provide a method for preparing the selective hydrogenation catalyst.
[0008] Another object of the present invention is to provide application of the selective hydrogenation catalyst.
[0009] The technical solution adopted to achieve the purpose of the present invention is:
[0010] A selective hydrogenation catalyst has a three-layer structure of core-transition metal-carbon shell, with a reducible oxide carrier as the core, a transition metal as the middle layer, and a polymerizable carbon source undergoing polymerization reaction to form the carbon shell.
[0011] The method for preparing the selective hydrogenation catalyst comprises the following steps:
[0012] The transition metal is loaded on a reducible oxide as a carrier by a wet chemical impregnation method to obtain a loaded catalyst precursor; then, a polymerizable carbon source is polymerized to form a carbon shell coating the surface of the loaded catalyst precursor, and after filtering, washing and drying, the catalyst is calcined in a non-oxygen atmosphere to obtain a selective hydrogenation catalyst, and the calcination temperature is 100 to 1000°C.
[0013] In the above technical solution, the carbon source is a nitrogen-containing carbon source or a nitrogen-free carbon source.
[0014] In the above technical solution, the nitrogen-containing carbon source is dopamine hydrochloride, glutamic acid or melamine, and the nitrogen-free carbon source is glucose or tannic acid.
[0015] In the above technical solution, the reducible oxide is TiO 2 、CeO 2 、FeOx(x=1–2)、Fe 2 O 3 , WO 3 , ZnO, CuO, ZrO or In 2 O 3 , the TiO 2 It has an anatase phase or a mixed phase of anatase and rutile.
[0016] In the above technical solution, the transition metal is a transition metal of VIII B, I B or IIB, and preferably, the transition metal is Pd, Pt, Ru, Au, Ni, Co or Fe.
[0017] In the above technical solution, the loading amount of the transition metal in the selective hydrogenation catalyst is 0.01wt.%-40.0wt.%.
[0018] In the above technical solution, the mass ratio of the carbon source to the supported catalyst precursor is (0.01-20.0):1.
[0019] In the above technical scheme, the polymerization coating is stirring polymerization coating, which is carried out in a water bath or an oil bath, with a stirring time of 6 to 72 hours, a water bath or an oil bath temperature of room temperature to 120°C, a stirring speed of 100 to 3000 r / min, and a hydrothermal polymerization coating temperature of.
[0020] In the above technical solution, the polymerization coating is hydrothermal polymerization coating, the temperature of the hydrothermal polymerization coating is 80-200°C, the time is 4-48h, the hydrothermal polymerization coating needs stirring or not, and when stirring, the stirring speed is 50-500r / min.
[0021] In the above technical solution, the drying is vacuum drying, the drying temperature is 60 to 120° C., and the drying time is 2 to 48 hours.
[0022] In the above technical solution, the non-oxygen atmosphere is H 2 and N 2 The mixed gas, H 2 The content is 1% vol~100% vol, N 2 To balance the gas.
[0023] Another aspect of the present invention also includes the use of the selective hydrogenation catalyst in the selective hydrogenation reaction of a compound containing two or more reducible functional groups at the same time.
[0024] In the above technical solution, the reducible functional group is C=C, -NO 2 、C≡C、C=O、-X(X is a halogen element)、-O-CH 3 , -C≡N, -OH and -CHO;
[0025] Preferably, when the reducible functional group is a C=O bond and a C=C bond, the compound subjected to the selective hydrogenation reaction is cinnamaldehyde or citronellal.
[0026] Another aspect of the present invention also includes the use of the selective hydrogenation catalyst in the selective catalytic hydrogenation of nitroaromatic hydrocarbons containing C=C to prepare aniline derivatives or nitrobenzene derivatives;
[0027] When the carbon source is a polymerizable nitrogen-containing carbon source:
[0028] The calcination temperature is 100-400℃, the C=C hydrogenation selectivity is 100%; the calcination temperature is 500-1000℃, -NO 2 The hydrogenation selectivity is 100%;
[0029] When the carbon source is a polymerizable nitrogen-free carbon source:
[0030] The calcination temperature is 100-300°C, the C=C hydrogenation selectivity is 100%; the calcination temperature is 400-1000°C, -NO 2 The hydrogenation selectivity was 100%.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] 1. The present invention proposes a method for preparing a carbon-coated selective hydrogenation catalyst with high activity and high selectivity. The catalyst is widely used in the selective hydrogenation reaction of raw materials for fine chemical products such as substituted 4-nitrophenylacetylene, 3-nitroacetylene, 3-nitrostyrene, ethyl 4-nitrocinnamate, and 4-nitrocinnamic acid.
[0033] 2. The structure of the selective hydrogenation catalyst prepared by the present invention is a three-layer structure of core-transition metal-carbon shell, that is, a reducible oxide carrier is used as the core, a polymerizable carbon source is polymerized to form a carbon shell, and a transition metal is used as the middle layer. By regulating the calcination temperature, the composition of the carbon shell layer can be regulated, thereby realizing the targeted catalytic hydrogenation reaction of the selective hydrogenation catalyst on nitroaromatic compounds containing other reducible functional groups; by regulating the calcination temperature, the selective catalytic hydrogenation reaction of a certain functional group of the above compound is realized, while other functional groups are retained from being hydrogenated. The preparation method of the selective hydrogenation catalyst is simple and can tolerate the environment. 2 , as well as CO in crude hydrogen sources, have excellent prospects for industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 It is a schematic diagram of the preparation process of the present invention.
[0035] Figure 2 This is a low-magnification TEM photograph of catalyst B prepared in Example 2 (magnification 40k).
[0036] Figure 3 This is a high-magnification TEM photograph of catalyst B prepared in Example 2 (magnification 400k). DETAILED DESCRIPTION
[0037] The present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0038] Example 1
[0039] A method for preparing a selective hydrogenation catalyst comprises the following steps:
[0040] like Figure 1 As shown, step 1, 410 mg of PdCl with a concentration of 0.115 mmol / g 2 The solution was added dropwise to 10 g of the carrier TiO 2 The powder was stirred to a slurry state, aged at 60 °C for 8 h, and dried at room temperature to obtain a supported catalyst precursor (Pd / TiO 2 Precursor), wherein the loading amount of Pd metal is 0.5wt.%.
[0041] Step 2, disperse 3g of the supported catalyst precursor in 600mL of Tris (trishydroxymethylaminomethane) buffer solution with a pH of 8.50 to obtain a suspension, dissolve 1.5g of the carbon source dopamine hydrochloride powder in 10g of deionized water to obtain an aqueous solution of dopamine hydrochloride, and add the aqueous solution of dopamine hydrochloride to the suspension in a water bath or oil bath under strong stirring at 40°C. After the addition is completed, continue stirring for 12h to obtain a material with a dopamine polymer shell layer, filter the material, wash with water and alcohol three times each, and dry at 60-100°C for 4-12h to obtain a polymer-coated material (black powder).
[0042] Step 3, placing the polymer-coated material in a quartz boat, placing the quartz boat in a tube furnace, and heating 8% vol H 2 and N 2 The mixed gas was introduced into a tubular furnace and heated at a rate of 5°C / min to 400°C for calcination for 180 min. After the calcination was completed and the mixture was cooled naturally, a selective hydrogenation catalyst coated with a carbon shell layer (finished catalyst A) was obtained.
[0043] Example 2
[0044] A method for preparing a selective hydrogenation catalyst, compared with Example 1, the calcination process in step 3 is heated to 500° C., and the other steps remain unchanged, to obtain a selective hydrogenation catalyst (catalyst B).
[0045] Example 3
[0046] A method for preparing a selective hydrogenation catalyst comprises the following steps:
[0047] Step 1: 410 mg of 0.115 mmol / g PdCl 2 The solution was added dropwise to 10 g TiO 2 The powder was stirred to a slurry state, aged at 60 °C for 8 h, and dried at room temperature to obtain a supported catalyst precursor (Pd / TiO 2 Precursor), wherein the loading amount of Pd metal is 0.5wt.%.
[0048] Step 2, dissolve 3g of glucose in 100mL of deionized water to obtain a glucose solution, disperse 1g of the supported catalyst precursor in the glucose solution, pour it into a polytetrafluoroethylene liner, place it in a stainless steel hydrothermal autoclave, and perform a hydrothermal reaction at 120°C for 8h. After natural cooling, filter, wash with water, and wash with alcohol three times each, and dry at 60-100°C for 4-12h to obtain a polymer-coated material (brown powder).
[0049] Step 3, placing the polymer-coated material in a quartz boat, placing the quartz boat in a tube furnace, and heating 8% vol H 2 and N 2 The mixed gas was introduced into a tubular furnace and heated at a rate of 5°C / min to 300°C for calcination for 180 min. After the calcination was completed and the temperature was naturally lowered, a selective hydrogenation catalyst (finished catalyst C) was obtained.
[0050] Example 4
[0051] A method for preparing a selective hydrogenation catalyst, compared with Example 3, the calcination process in step 3 is heated to 400° C., and the other steps remain unchanged, to obtain a selective hydrogenation catalyst (catalyst D).
[0052] Comparative Example 1
[0053] A method for preparing a catalyst comprises the following steps:
[0054] Step 1: 410 mg of 0.115 mmol / g PdCl 2 The solution was added dropwise to 10 g of TiO 2 The powder was stirred to a slurry state, aged at 60° C. for 8 h, and dried at room temperature to obtain a supported catalyst precursor, wherein the loading amount of Pd metal was 0.5 wt.%.
[0055] Step 2, placing the supported catalyst precursor in a quartz boat, placing the quartz boat in a tube furnace, and adding 8% vol H 2 and N 2 The mixed gas was introduced into a tubular furnace, and the heating rate was set at 5°C / min. The temperature was raised to 300°C for calcination. The calcination time was 180 min. After the calcination was completed and the temperature was naturally lowered, a brown-grey catalyst powder (catalyst E) was obtained.
[0056] Comparative Example 2
[0057] A method for preparing a catalyst, compared with comparative example 1, the calcination process in step 2 is heated to 400° C., and the other steps remain unchanged, to obtain a catalyst (catalyst F).
[0058] Comparative Example 3
[0059] A method for preparing a catalyst, compared with comparative example 1, the calcination process in step 2 is heated to 500° C., and the other steps remain unchanged, to obtain a catalyst (catalyst G).
[0060] Test Case
[0061] Catalysts A, B, C and D prepared in the examples and catalysts E, F and G prepared in the comparative examples were evaluated for catalytic performance under the same reaction conditions. The results are shown in Table 2. The reaction conditions were as follows: the hydrogen source was high-purity hydrogen or H containing 1000 ppm CO. 2 and CO mixed gas, the reaction temperature is 40 ° C, the reaction pressure is 3 bar, the stirring speed is 2500 r / min, the reaction substrate is 3-nitrostyrene (3-NitroStyrene, 3-NS); the reaction product is detected by Shimadzu GC-2014C, the chromatographic column is HP-5 (0.32 mm, 50 m), and the conversion rate, selectivity and TOF calculation formula are as follows:
[0062] Conversion rate calculation formula:
[0063]
[0064] Selectivity calculation formula:
[0065]
[0066]
[0067]
[0068] TOF calculation formula
[0069]
[0070] Among them, time represents time, c 3-NS,0 : The concentration of substrate 3-NS before the reaction, c 3-NS,t : The concentration of substrate 3-NS after the reaction, c 3-VA :After the reaction, -NO 2 The concentration of the hydrogenation product 3-vinylaniline (3-VA), c 3-ENB : After the reaction, the concentration of the C=C double bond hydrogenation product 3-nitroethylbenzene (3-ethylnitrobenzene, 3-ENB), c 3-EA After the reaction, the complete hydrogenation product is 3-ethylaniline, i.e. C=C and -NO 2 The concentration of the product after hydrogenation is complete, n 3-NS,0 : The amount of substrate 3-NS before the reaction, n 3-NS,t : The amount of substrate 3-NS after the reaction, n Pd : The amount of substance in the active center of the Pd element in the catalyst, calculated based on the total amount.
[0071] Table 2
[0072]
[0073]
[0074] Among them, a: the amount of 3-NS substance is 0.25mmol, the amount of catalyst is 5mg, the reaction time is 3min, and high-purity hydrogen is the hydrogen source; b: the amount of 3-NS substance is 0.25mmol, the amount of catalyst is 5mg, the reaction time is 3min, H 2 and CO mixed gas as hydrogen source, CO content 1000ppm; c: 3-NS substance amount is 0.25mmol, catalyst amount is 10mg, reaction time is 30min, high purity hydrogen is hydrogen source; d: 3-NS substance amount is 0.25mmol, catalyst amount is 10mg, reaction time is 30min, H 2 The mixed gas with CO is the hydrogen source, and the CO content is 1000ppm.
[0075] As shown in Table 2, for the catalysts prepared at different calcination temperatures, the catalysts A and B prepared in the example, using the same carbon source, dopamine hydrochloride powder (nitrogen-containing carbon source), have a C=C hydrogenation selectivity close to 100% at low temperatures (100-400°C); at high temperatures (500-1000°C), -NO 2 The hydrogenation selectivity is close to 100%; for the catalysts prepared at different calcination temperatures, catalyst C and catalyst D prepared in the example, using the same carbon source glucose (without nitrogen carbon source), at low temperature (100-300°C), the C=C hydrogenation selectivity is close to 100%; at high temperature (400°C-1000°C), -NO 2 The hydrogenation selectivity is close to 100%; this is because the carbon source containing nitrogen has a relatively thick carbon shell and a relatively stable structure due to the presence of nitrogen. When glucose is used as a carbon source, it is easier to be reduced. Therefore, the carbon source without nitrogen has a lower conversion temperature. At the same time, the results of catalyst A and catalyst B under two reaction conditions a and b show that CO does not significantly poison the catalyst.
[0076] When the same carbon source is calcined at high temperature, the sp2 hybridized C disappears and oxygen-containing carbon appears. Therefore, -NO 2 The hydrogenation selectivity is close to 100%; during low-temperature calcination, there is sp2 hybridized C without oxygen-containing carbon, so the C=C hydrogenation selectivity is close to 100%.
[0077] Catalysts E, F and G prepared in comparative examples show that at different calcination temperatures, the non-carbon-coated materials do not have such a change in selectivity, and the C=C hydrogenation selectivity is close to 100%.
[0078] The activity of the catalysts is different when catalyzing the hydrogenation of different functional groups. When catalyst A, catalyst C, catalyst E, catalyst F and catalyst G all selectively catalyze C=C hydrogenation, the TOF (turnover frequency, the number of times a unit catalyst active site can catalyze reactions per unit time) of catalyst A and catalyst C is greater.
[0079] If the reaction substrate is replaced with 4-nitrophenylacetylene, 3-nitrophenylacetylene, 3-nitrostyrene, ethyl 4-nitrocinnamate, 4-nitrocinnamic acid, etc., the catalytic results are the same as above.
[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A selective hydrogenation catalyst, characterized in that The selective hydrogenation catalyst is a three-layer structure of core-transition metal-carbon shell, with a reducible oxide carrier as the core, a transition metal as the middle layer, and a polymerizable carbon source undergoing polymerization reaction to form the carbon shell.
2. The method for preparing a selective hydrogenation catalyst according to claim 1, characterized in that: The following steps are involved: Using a reducible oxide as a carrier, a wet chemical impregnation method is used to load the transition metal to obtain a supported catalyst precursor; Then, the polymerizable carbon source is polymerized to form a carbon shell which is coated on the surface of the supported catalyst precursor, filtered, washed, dried, and then calcined in a non-oxygen atmosphere to obtain a selective hydrogenation catalyst, wherein the calcination temperature is 100-1000°C.
3. The preparation method according to claim 2, characterized in that: The carbon source is a nitrogen-containing carbon source or a nitrogen-free carbon source; the nitrogen-containing carbon source is dopamine hydrochloride, glutamic acid or melamine, and the nitrogen-free carbon source is glucose or tannic acid.
4. The preparation method according to claim 2, characterized in that: The reducible oxide is TiO2, CeO2, FeOx (x=1-2), Fe2O3, WO3, ZnO, CuO, ZrO or In2O3, and the TiO2 has an anatase phase or a mixed phase of anatase and rutile.
5. The preparation method according to claim 2, characterized in that: The transition metal is a transition metal of VIII B, I B or IIB, preferably, the transition metal is Pd, Pt, Ru, Au, Ni, Co or Fe.
6. The preparation method according to claim 2, characterized in that: The loading amount of the transition metal in the selective hydrogenation catalyst is 0.01wt.%-40.0wt.%; the mass ratio of the carbon source to the supported catalyst precursor is (0.01-20.0):
1.
7. The preparation method according to claim 2, characterized in that: The polymerization coating is stirring polymerization coating or hydrothermal polymerization coating; When the coating is carried out by stirring polymerization, the stirring polymerization is carried out in a water bath or an oil bath, the stirring time is 6 to 72 hours, the temperature of the water bath or the oil bath is room temperature to 120° C., and the stirring speed is 100 to 3000 r / min; When the hydrothermal polymerization coating is used, the temperature of the hydrothermal polymerization coating is 80-200° C., the time is 4-48 hours, and the hydrothermal polymerization coating needs stirring or no stirring. When stirring, the stirring speed is 50-500 r / min.
8. Use of the selective hydrogenation catalyst according to claim 1 in the selective hydrogenation reaction of a compound containing two or more reducible functional groups at the same time.
9. The use according to claim 8, characterized in that: The reducible functional groups are C=C, -NO2, C≡C, C=O, -X (X is a halogen element), -O-CH3, -C≡N, -OH and -CHO; Preferably, when the reducible functional group is a C=O bond and a C=C bond, the compound subjected to the selective hydrogenation reaction is cinnamaldehyde or citronellal.
10. Use of the selective hydrogenation catalyst according to claim 1 in the selective catalytic hydrogenation of nitroaromatic hydrocarbons containing C=C to prepare aniline derivatives or nitrobenzene derivatives, characterized in that: When the carbon source is a polymerizable nitrogen-containing carbon source: The calcination temperature is 100-400°C, the C=C hydrogenation selectivity is 99%-100%; the calcination temperature is 500-1000°C, the -NO2 hydrogenation selectivity is 99%-100%; When the carbon source is a polymerizable nitrogen-free carbon source: The calcination temperature is 100-300°C, and the C=C hydrogenation selectivity is 99%-100%; the calcination temperature is 400-1000°C, and the -NO2 hydrogenation selectivity is 99%-100%.
Citation Information
Patent Citations
Preparation of non-precious metal nitric oxide storage reduction catalyst LaMnO3 / K / ZrTiO4 and application thereof
CN102179242A
Nanocarbon-loaded high-dispersion platinum catalyst, as well as preparation method of catalyst and application of catalyst to hydrogenation reaction of aromatic nitro-compounds
CN109876801A
Preparation method of supported catalyst for synthesizing chloroaniline through catalytic hydrogenation of chloronitrobenzene
CN109939713A
Sub-nano Pt selective hydrogenation catalyst, preparation method and application thereof
CN114471540A
An electronic device for determining whether to apply a prediction algorithm using acceleration of touch input and / or angular acceleration of the touch input and control method thereof
KR1020220109250A